2021
DOI: 10.1021/acs.iecr.1c01111
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Development of Various Oxygen Carriers for the Chemical Looping Combustion Process: A Review

Abstract: The amount of CO 2 in the atmosphere is rising due to the combustion of fossil fuels to fulfill the energy demand. The need to build cleaner and more efficient energy systems is motivated by the introduction of chemical looping combustion (CLC) as an alternative to conventional combustion by transferring oxygen. The transfer of oxygen from the air to fuel is carried out by a metal oxide known as an oxygen carrier (OC). For high fuel conversion and oxygen transport capacity, many efforts have been made for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 136 publications
(184 reference statements)
0
67
0
Order By: Relevance
“…Similarly, there are many publications that deal with the use of manganese ores as OC materials in CLC. In comparison to ilmenite, manganese ore achieved a significantly higher rate of fuel gasification and higher gas conversion, while fine production was higher. ,, High reactivity of manganese ores is often related to the catalytic effect of impurities (such as alkali particles) that causes cavitations in the solid char and improves char gasification rates as a consequence. , It should be noted that the alkali effect is not sustainable over multiple redox cycles because alkali can be lost with ash. For this reason, it is important to study the ore under long circulation periods at a pilot scale.…”
Section: Oc Performances: Ilmenite Versus Mn Oresmentioning
confidence: 99%
“…Similarly, there are many publications that deal with the use of manganese ores as OC materials in CLC. In comparison to ilmenite, manganese ore achieved a significantly higher rate of fuel gasification and higher gas conversion, while fine production was higher. ,, High reactivity of manganese ores is often related to the catalytic effect of impurities (such as alkali particles) that causes cavitations in the solid char and improves char gasification rates as a consequence. , It should be noted that the alkali effect is not sustainable over multiple redox cycles because alkali can be lost with ash. For this reason, it is important to study the ore under long circulation periods at a pilot scale.…”
Section: Oc Performances: Ilmenite Versus Mn Oresmentioning
confidence: 99%
“…The CL process builds upon the ability of an oxygen carrier (OC) to perform redox reactions in separate reactors or reaction stages 16 . Over numerous materials that have been studied as an oxygen carrier, Cu, Mn, Co, Ni, and Fe are the most feasible metals used for the CL process to date 27 . Several terms have been used to classify the CL process based on its particular objective, such as CL combustion 19;28;29;30 , CL gasification 31 , CL reforming 25;32;33 , CL air separation 34;35 , or based on how the oxygen is transferred such as chemical looping with oxygen uncoupling (CLOU) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…), or for utilizing biomass material as feed 26 . The exploration of OC materials that have long lifetime, excellent reactivity, and lower cost, is still an area of interest in CL research 27 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Reports have revealed that oxygen transfer capacity and oxygen transfer rate are the most critical factors in selecting OCs. 15,16 In general, synthetic OCs consist of single metal oxides (the widely used type is the first-row transition metal oxides), mixed metal oxides, and inert support oxides. Due to their low cost and strong mechanical strength, natural occurrences such as ilmenite, olivine, iron ore, and waste materials from the industry (bauxite waste, ash, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For the past 10 years, researchers have examined various kinds of OCs that are inexpensive, thermally stable, possess good oxygen transport capacity (OTC), thermally stable, have improved mechanical strength, and better gas selectivity with a low environmental effect . Reports have revealed that oxygen transfer capacity and oxygen transfer rate are the most critical factors in selecting OCs. , …”
Section: Introductionmentioning
confidence: 99%